The implementation of health istithaah to the pilgrims with tuberculosis: a cross-sectional study in Jakarta, Indonesia (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Based on the regulation of the Indonesian Ministry of Health No. 15 of 2016 about health istithaah for the Hajj, patients with tuberculosis (TB) can be categorized into ineligible or temporarily ineligible pilgrims. This study aimed to know the characteristics of pilgrims with TB and determined their level of fitness for fulfilling the health istithaah. METHODS A cross-sectional study of pilgrims from Jakarta who were receiving TB treatment during the Hajj in 2018 was conducted with consecutive sampling. The secondary data was collected from the Hajj Integrated Computer Health System 2018, TB registered form, and six-minute walk test (the fitness level data) conducted by the District Hajj Health Team at district health centers in DKI Jakarta and Pondok Gede before the Hajj embarkation in June–July 2018. The questionnaire to the Indonesian Hajj Health Team during pilgrimage was also included as additional data. RESULTS Thirty-one pilgrims received TB treatment and completed the intensive phase of TB treatment, but 29 pilgrims had no symptoms. Among them, 2 patients had MDR-TB. Most of them were male aged ≥40 years old. Twelve pilgrims with TB have a sufficient fitness. All pilgrims were able to run the pillars of the Hajj. CONCLUSIONS Pilgrims with TB, including MDR-TB, who had completed the intensive phase with a negative sputum smear test were declared eligible for the Hajj with assistance.